Professional Competence of Teachers in Learning Music at Elementary Schools in Pontianak - Ghozali, Imam (Harmonia: Journal of Arts Research and Education, 2020)
Learning the art of music that has characteristics, special characters, and is carried out within an integrative thematic frame in elementary schools, needs to be supported by the professional competence of classroom teachers. The purpose of this study was to determine the professional competence of classroom teachers in learning music in elementary schools. This paper is the result of interpretive descriptive research with the main data source of classroom teachers, while the source of supporting data are students and principals. Data collection techniques are done by tests, observations, and interviews. The data collection process is carried out starting before the learning stage until the learning evaluation process. Based on the results of the study showed that: (1) the average mastery of classroom teachers to the knowledge of music theory needed in learning has only reached 45%; (2) the average teacher mastery of musical basic competencies has only reached 42.5%; and (3) the average teacher mastery of musical instrument playing skills competencies needed in learning has only reached 33.75%. The results of tests conducted on the teachers turned out to be relevant to the data obtained during the implementation of learning. It was proven that learning material in the form of musical knowledge such as music symbols, time bars, and various tempos is only taught by one class teacher. The practice of singing traditional songs is not supported by the teacher’s ability to give examples of reading song notation in accordance with the demands of the teacher’s handbook. Practical learning material for playing musical instruments is also only implemented by one classroom teacher. The implementation of music art learning in which most of the time allocation is filled with singing songs that are mastered (memorized) by the teacher. This shows that the classroom teacher in the implementation of music art learning has not been supported by adequate professional competence.